Identifying degradation pathways at Sembrong Dam, Johor: insights from Sentinel-2 satellite imagery and NDVI analysis - Anjang Ahmad, Mustafa; Kahlid, Muhammad Dzikri; Mohd Hussin, Muhammad Haziq Izzuddin; Mohammad Razi, Mohd Adib; Hussein Al-Qadami, Ebrahim Hamid; Cahyadi, Mokhamad Nur (SINERGI, 2025)
The study is to evaluate the catchment area mapping at Sembrong Dam in Johor, Malaysia and identify potential transit pathways contributing to dam water degradation while implementing targeted mitigation works. The analysis involved the surface runoff patterns and topographical/geographic data via a digital elevation model (DEM), providing insights into terrain characteristics, slope, and flow directions to hydrological dynamics that significantly contribute to water resource management. This study focuses on producing the catchment area map with satellite imagery and defining the transit pathway that potentially causes water degradation in a reservoir. The analysis uses satellite images from sentinel-2 processing to generate a detailed runoff map and DEM of the catchment area surrounding the dam. The study uses Red Bands (RED) and Near-Infrared Bands (NIR) to process sentinel satellite images to create NDVI maps. Data is uploaded as Raster data in QGIS, and NDVI calculations are performed to transform raw satellite data into an index for vegetation health. NDVI values are classified into different colour classes to visualize the condition of the study area. High NDVI values indicate higher concentrations of agriculture nutrients, potentially triggering eutrophication in watersheds through surface runoff. The study analyzed a 66.89 km2 reservoir catchment area using runoff maps. NDVI analysis showed vegetation density and plant health, with robust vegetation in the dam-surrounded region with an NDVI value of 0.8. However, due to its narrow geography and deep lakes, the northeastern region is slightly polluted and susceptible to algae growth. The study aims to improve understanding of LULC and water conditions by analyzing pollution levels using remote sensing data, DEM, and NDVI for mitigation strategies.